An Integrated Approach Based on Network Analysis Combined With Experimental Verification Reveals PI3K/Akt/Nrf2 Signaling Is an Important Way for the Anti-Myocardial Ischemia Activity of Yi-Qi-Tong-Luo Capsule - Duan, Huxinyue; Li, Meiyan; Liu, Jia; Sun, Jiayi; Wu, Chunjie; Chen, Yu; Guo, Xiaohui; Liu, Xinglong (Frontiers in Pharmacology, 2022)
Background:Yiqi-Tongluo Capsule (YTC) is a Chinese traditional patent medicine that has been used in the treatment of myocardial ischemia (MI). However, its molecular mechanisms against MI have not been clear. Methods: Network analysis and experimental verification were used to explore the potential molecular mechanisms of YTC for MI treatment. Firstly, the main components in the capsules and the potential targets of these components were predicted by online databases. The MI related genes were collected from Genecards and Online Mendelian Inheritance in Man (OMIM) databases. The drug targets and disease targets were intersected, and then the protein-protein interaction (PPI) and Drug-Molecular-Target-Disease Network (DMTD) were constructed, and GO enrichment analysis and KEGG pathway enrichment analysis were performed. Based on the H2O2-stimulated H9c2 cells, flow cytometry, western blot (WB) and immunofluorescence experiments were performed to verify the network analysis prediction. Results: A total of 100 active components and 165 targets of YTC were predicted, in which there were 109 targets intersected with the targets of MI. GO and KEGG analysis showed that these potential targets were related to a variety of biological processes and molecular mechanisms, including oxidative stress and PI3K/AKT pathway. Astragaloside IV (AS IV) and paeoniflorin (PAE) might be the main active components in YTC. The results of cell counting kit-8 (CCK-8) showed that YTC alleviated the damage of H2O2 to H9c2 cells. The results of flow cytometry, DAPI staining and JC-1 probe showed that YTC alleviated H2O2 induced apoptosis in H9c2 cells. In addition, YTC reduced the level of intracellular superoxide anion, increased the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px), and reduced the content of malondialdehyde (MDA) in H2O2-induced H9c2 cells. The results of immunofluorescence and WB showed that the phosphorylation of PI3K and Akt were increased, the expression of Bcl-2 was up-regulated and the expression of cleaved caspase-3 and Bax were down-regulated. Besides, the nuclear translocation of Nrf2 were increased. Conclusion: In conclusion, the results of this study showed that YTC might alleviate MI by suppressing apoptosis induced by oxidative stress via the PI3K/Akt/Nrf2 signal pathway.